1997
DOI: 10.1177/107906329700900405
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Self-Esteem of Child Molesters

Abstract: Thirty-two child molesters received self-esteem enhancement procedures as part of an overall treatment program. The effects of the self-esteem procedures were evahiated in terms of changes on the Social Self-esteem Inventory. It was found that the procedures significantly enhanced self-esteem. These changes were significantly related to reductions in loneliness and increases in intimacy but were unrelated to improvements in victim empathy despite the fact that victim empathy and self-esteem scores were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 48 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…7, 85-96 (2000) 91 several times each day. This overall approach has been shown to effectively enhance self-esteem (Marshall et al, 1997b).…”
Section: Assessment and Treatment Of Sexual Offendersmentioning
confidence: 98%
“…7, 85-96 (2000) 91 several times each day. This overall approach has been shown to effectively enhance self-esteem (Marshall et al, 1997b).…”
Section: Assessment and Treatment Of Sexual Offendersmentioning
confidence: 98%
“…McGrath, Hoke, and Vijtisek (1998) obtained similar results when they compared cognitive±behavioral treatment and nonspeci®c mental health treatment. Other researchers (e.g., Marshall et al, 1997) have also reported treatment eects.…”
Section: Treatment Effectivenessmentioning
confidence: 93%
“…Freund (1990) described rape as the result of speci®c, interpersonal de®cits (i.e., courtship failure). Marshall and his colleagues (Marshall, Turner & Barbaree, 1989;Marshall, 1993;Ward, McCormack, & Hudson, 1997) have described diculties with intimacy and loneliness as well as self-esteem (Marshall, Champange, Sturgeon, & Bryce, 1997); others have pointed to larger social processing de®cits (Johnson & Ward, 1996). Many have described cognitive processes that are distorted (e.g., Bumby, 1996), but it is unclear whether the distortions preceded and facilitated the sexual violence or were oered as defenses when the perpetrator was held to account.…”
Section: Who Are Sex Offenders?mentioning
confidence: 99%
“…Sex offenders are generally regarded as having low self-esteem, which it is believed may contribute to their offending and hinder progress in therapy. Finkelhor (1984) and Groth (1979) have suggested that low self-esteem and sex offending are related, while Marshall, Champagne, Sturgeon and Bryce (1997) found that enhancement of self-esteem facilitated the attainment of a number of specific treatment goals and was associated with reductions in deviant arousal. Fisher et al (1999) found significantly lower levels of self-esteem in child abusers compared to non-offenders.…”
Section: Socoeffectve Problemsmentioning
confidence: 99%